TINJAUAN SISTEMATIS PENGEMBANGAN SISTEM INFORMASI DOKUMENTASI BERBASIS WEB (2021-2025) - Kadek Siva Ayu, Ni; Muhammad Fahrury, Romdendine; Priati, Assiroj (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study presents a systematic review of research on web application development and testing methods conducted between 2021 and 2025 using the PRISMA method. From searches across three databases, namely Garuda, Google Scholar, and Open Alex, a total of 13,642 articles were identified and subsequently filtered down to 20 selected studies. The aim of this study is to identify the development methods, testing methods, system modeling, software, and database systems used in the development of web-based documentation information systems. The findings indicate that the Waterfall method is the most widely applied (65%), followed by the Prototyping and Agile methods. Black Box testing dominates as the primary testing method, while UML serves as the standard for system modeling. PHP-based technology is the most dominant software choice, and MySQL remains the absolute most commonly used database system.